IMPLEMENTATION OF PHYSICAL EDUCATION AND EARLY CHILDHOOD SPORTS - Nurul Amaliya Annida Azis; Suaib Nur; Nurdin Salama (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
Implementation of physical education and early childhood sports is an integral part of overall education that contributes to individual development through physical activity of natural human movement. Physical education is a planned and designed sequence of learning experiences to meet the developmental and growth, and behavioral needs of each child. Physical education starts from an early age to stimulate growth. The purpose of this study was to find out the implementation of physical education and sports for early childhood in PAUD schools in the city of Palopo in 2022. This study used a survey method with a qualitative descriptive analysis approach. The sample is PAUD teachers in the city of Palopo with a total of 60 people taken by random sampling. Data collection using a questionnaire. Based on the results of data analysis, it can be concluded that the implementation of physical education and sports for early childhood at PAUD schools in Palopo City has been carried out properly